Paeonol Attenuates LPS-Induced Endothelial Dysfunction and Apoptosis by Inhibiting BMP4 and TLR4 Signaling Simultaneously but Independently - Choy, Ker Woon; Lau, Yeh Siang; Murugan, Dharmani Devi; Vanhoutte, Paul M.; Mustafa, Mohd Rais (American Society for Pharmacology and Experimental Therapeutics, 2017)
Inflammatory injury of the endothelium leads to apoptosis and endothelial dysfunction. The current study explored the effect and mechanisms of paeonol in inflammation-induced apoptosis and endothelial dysfunction induced by lipopolysaccharides (LPSs). The effects of paeonol on LPS-induced inflammatory injury were assessed by Western blotting, flow cytometry and reactive oxygen species (ROS) measurement in human umbilical vein endothelial cells (HUVECs) and C57BL/6J mice. Vascular reactivity of isolated mouse aortae was examined using wire myographs. The exposure of HUVECs to LPS increased the protein presence of Toll-like receptor 4 (TLR4), bone morphogenic protein 4 (BMP4), BMP receptor type 1A, nicotinamide adenine dinucleotide phosphate oxidase subunit 2, mitogen-activated protein kinase (MAPK), inducible nitric oxide synthase (iNOS), and cleaved caspase 3, as well as decreased it in phosphorylated endothelial nitric oxide synthase; these effects were prevented by treatment with paeonol. Similarly, cotreatment with paeonol reversed BMP4-induced apoptosis in HUVECs. Relaxation in response to the endothelium-dependent vasodilator acetylcholine were impaired in mouse aortae after exposure to LPSs; this endothelial dysfunction was reversed by cotreatment with paeonol, noggin (a BMP4 inhibitor), TAK242 (TLR4 antagonist), apocynin (an ROS scavenger), MAPK inhibitors, and AG (an iNOS inhibitor). BMP4 small interfering RNAs (siRNAs) abolished LPS-induced upregulation of BMP4 and cleaved caspase 3 protein, but not in cells treated with TLR4 siRNA and vice versa. The silencing of TLR4 and BMP4 abolished the inhibitory effects of paeonol on LPS-induced activation of cleaved caspase 3. The present results demonstrate that paeonol reduces LPS-induced endothelial dysfunction and apoptosis by inhibiting TLR4 and BMP4 signaling independently.